Peningkatan Keterampilan Menulis Deskripsi dengan Menggunakan Strategi Mind Map di Sekolah Dasar - Rahmatina , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
Descriptive writing is one of the language skills that should be master by Elementary School Students. Based on the researher’s observation, it was found that the students’ descriptive writing ability is insufficient. It was caused by inappropriate teacher’s strategy. The researcher uses mind map startegy to help the students in descriptive writing. The aim of this research is to find out the improvement of the third grade students at Public Elementary School 08 Tarok Dipo Bukittingi. This research is action research. Subject of this research is the thrid grade students at Public Elementary School 08 Tarok Dipo Bukittingi, it was 37 students. Data of this research is the students activities during teaching and learning process. The result of this research is the use of mind map strategy can improve the students’ descriptive writing ability. The students seem enthusiastic and motivated in learning. The students are easy to write their ideas by using mind map strategy. The students able to write their ideas in descriptive writing well.